Factors Associated with Self-Management in Adolescents with Type 1 Diabetes - Alaee Karahroudy, Fatemeh; Mohammadi Shahboulaghi, Farahnaz; Ali Hosseini, Mohammad; Rasouli, Maryam; Biglarian, Akbar (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Diabetes is one of the most common chronic diseases that is also highly prevalent among adolescents. The present study was conducted to determine the relationship between demographic characteristics and self-management in adolescents with type 1 diabetes. Methods: This descriptive-analytical study was conducted on 426 adolescents with type 1 diabetes aged 13 to 18, and diagnosed for at least one year. The research tools included a demographic information form covering the patients’ personal, family, and health details, and the Self-Management of type 1 Diabetes in Adolescence (SMOD-A) with five subscales of collaboration with parents, diabetes care activities, diabetes problem-solving, diabetes communication, and diabetes goals. The content validity of the measure was then evaluated by a group of experts and found to be acceptable (SCVI = 98%). In the assessment of the measure›s reliability, the intraclass correlation showed an overall Cronbach’s alpha of 0.88. The test-retest showed a consistency of 0.73 for the measure. Results: The results obtained showed that the presence of another diabetic member in the family leads to higher levels of self-management in some dimensions, including problem-solving, communication, and goals, yet to lower levels in some others, including collaboration with parents and diabetes care activities. A direct relationship was observed between the duration of time since the diagnosis and the scores obtained by the adolescents. An inverse relationship was observed between the type of physician in charge and the scores obtained in the subscales of collaboration with parents, problem-solving, communication, and goals. The scores obtained were directly related to having a school health record and having access to diabetic care tools at school. Family income was found to be directly related to diabetes care activities and inversely to problem-solving, communication and goals. P of ≤ 0.05 was considered significant for all relationships. Conclusions: Self-management was found to be moderate to good among Iranian adolescents with type 1 diabetes; however, it could be further improved with the support of both families and medical teams involved.